2020
DOI: 10.1038/s41467-020-14518-3
|View full text |Cite
|
Sign up to set email alerts
|

A molecular gradient along the longitudinal axis of the human hippocampus informs large-scale behavioral systems

Abstract: The functional organization of the hippocampus is distributed as a gradient along its longitudinal axis that explains its differential interaction with diverse brain systems. We show that the location of human tissue samples extracted along the longitudinal axis of the adult human hippocampus can be predicted within 2mm using the expression pattern of less than 100 genes. Futhermore, this model generalizes to an external set of tissue samples from prenatal human hippocampi. We examine variation in this specifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
89
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 62 publications
13
89
1
Order By: Relevance
“…Here, our data not only complements gene expression studies (Bienkowski et al, 2018; Cembrowski et al, 2016; H. W. Dong et al, 2009; Lein et al, 2007; Thompson et al, 2008), but shows neurochemical heterogeneity in line with different functional connectivity along the dorsal‐ventral axis (Anacker & Hen, 2017; Bannerman et al, 2014; Bast, Wilson, Witter, & Morris, 2009; Kheirbek et al, 2013; Lee, Kim, Cho, Kim, & Park, 2017; Moser & Moser, 1998; Strange et al, 2014). Further, our findings of different as well as indifferent (co‐) distributions of specific neurotransmitter receptors along the dorsal‐ventral axis may offer a link between the dichotomy of functionally segregated subfields with precise borders on the one hand and a more gradual organization of processing functions on the other and show that both views are not exclusive (Bast et al, 2009; Brun et al, 2008; Lee, Rao, & Knierim, 2004; Leutgeb, Leutgeb, Moser, & Moser, 2005; Leutgeb, Leutgeb, Moser, & Moser, 2007; McHugh et al, 2007; Neunuebel & Knierim, 2014; Strange et al, 2014; Vogel et al, 2020). Despite ubiquitous glutamatergic and GABAergic inputs to all hippocampal subdivisions (Amaral et al, 2007; Freund & Buzsáki, 1996; Klausberger, 2009; Klausberger & Somogyi, 2008; Kouvaros & Papatheodoropoulos, 2016) we could separate dorsal, intermediate and ventral subdivisions by disseminative quantities of AMPA, Kainate, NMDA, mGlu 2/3 , GABA A , and GABA A(BZ) binding sites, likely reflecting different types of cells and/or cellular properties in these areas in addition to different outputs to other cortical and subcortical areas as well as intra‐hippocampal connectivity (Besnard, Miller, & Sahay, 2020; Bienkowski et al, 2018; Cembrowski et al, 2016; Nakashiba, Young, McHugh, Buhl, & Tonegawa, 2008; Nakazawa, McHugh, Wilson, & Tonegawa, 2004; Scharfman & Myers, 2012; Wheeler et al, 2015; Witter & Amaral, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Here, our data not only complements gene expression studies (Bienkowski et al, 2018; Cembrowski et al, 2016; H. W. Dong et al, 2009; Lein et al, 2007; Thompson et al, 2008), but shows neurochemical heterogeneity in line with different functional connectivity along the dorsal‐ventral axis (Anacker & Hen, 2017; Bannerman et al, 2014; Bast, Wilson, Witter, & Morris, 2009; Kheirbek et al, 2013; Lee, Kim, Cho, Kim, & Park, 2017; Moser & Moser, 1998; Strange et al, 2014). Further, our findings of different as well as indifferent (co‐) distributions of specific neurotransmitter receptors along the dorsal‐ventral axis may offer a link between the dichotomy of functionally segregated subfields with precise borders on the one hand and a more gradual organization of processing functions on the other and show that both views are not exclusive (Bast et al, 2009; Brun et al, 2008; Lee, Rao, & Knierim, 2004; Leutgeb, Leutgeb, Moser, & Moser, 2005; Leutgeb, Leutgeb, Moser, & Moser, 2007; McHugh et al, 2007; Neunuebel & Knierim, 2014; Strange et al, 2014; Vogel et al, 2020). Despite ubiquitous glutamatergic and GABAergic inputs to all hippocampal subdivisions (Amaral et al, 2007; Freund & Buzsáki, 1996; Klausberger, 2009; Klausberger & Somogyi, 2008; Kouvaros & Papatheodoropoulos, 2016) we could separate dorsal, intermediate and ventral subdivisions by disseminative quantities of AMPA, Kainate, NMDA, mGlu 2/3 , GABA A , and GABA A(BZ) binding sites, likely reflecting different types of cells and/or cellular properties in these areas in addition to different outputs to other cortical and subcortical areas as well as intra‐hippocampal connectivity (Besnard, Miller, & Sahay, 2020; Bienkowski et al, 2018; Cembrowski et al, 2016; Nakashiba, Young, McHugh, Buhl, & Tonegawa, 2008; Nakazawa, McHugh, Wilson, & Tonegawa, 2004; Scharfman & Myers, 2012; Wheeler et al, 2015; Witter & Amaral, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this view, key fibre pathways in the MTL, notably the perforant pathway, mossy fibres, and Schaffer collaterals, are typically defined by their relation to hippocampal subfields (subiculum, CA1-4, dentate gyrus) that are sequentially organised along the iso-to-allocortical axis ( Amaral and Witter, 1989 ). In addition to the iso-to-allocortical shifts that follow hippocampal infolding, neurobiological and functional properties of the MTL system also appear to be organised with respect to a second, anterior-posterior axis ( Amaral and Witter, 1989 ; Strange et al, 2014 ; Witter et al, 2006 ; Poppenk et al, 2013 ; Vogel et al, 2020 ). Tract-tracing studies in rodents have shown that anterior-posterior gradients determine hippocampal connectivity to entorhinal cortices ( Witter et al, 2006 ) and functional neuroimaging studies in humans have illustrated distinct combinations of anterior-posterior and lateral-medial topographies in the entorhinal and parahippocampal cortex ( Navarro Schröder et al, 2015 ; Maass et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…We particularly note that this step is of particular importance as multiple examinations have pointed out general (i.e. global) posterior-anterior gradients of expression levels across brain areas (McColgan et al, 2018; Vogel et al, 2020), effects that may more reflect spatial patterns general to genes expressed in the brain, rather than reflecting patterns unique to the GOI. With transcriptomic datasets such as AHBA generally containing data of ~20,000 genes, it is important to go beyond statistical testing of a spatial association between the expression pattern of a GOI and the cortical pattern of a phenotype of interest.…”
Section: Resultsmentioning
confidence: 99%